Capacity Analysis of Urban Drainage Channels Using the Storm Water Management Model (SWMM): A Case Study of Jalan Raya Puputan - Ni Komang Manik Trisnasari; I Gusti Ngurah Hesa Respati Haditama; Ni Komang Armaeni (Departemen Teknik Sipil dan Lingkungan IPB, 2026)
Urban flooding frequently occurs in areas with high rainfall intensity and limited drainage capacity. The Plaza Renon area in Denpasar City has experienced recurrent inundation events during heavy rainfall, particularly along Jalan Raya Puputan. These conditions indicate that the existing drainage system may not be capable of conveying runoff effectively. Therefore, this study aims to evaluate the capacity of the existing drainage channels and propose improvements to enhance their hydraulic performance. The research was conducted through hydrological and hydraulic analyses. Hydrological analysis included rainfall data quality testing, rainfall frequency analysis using the Gumbel distribution, rainfall intensity analysis using the Mononobe method, and estimation of design discharge using the Rational Method. Hydraulic analysis was then performed through drainage network modeling using EPA SWMM version 5.2. The developed model consisted of 48 subcatchments, 67 junctions, 74 conduits, and one outfall. The simulation results indicate that several drainage channels are unable to accommodate runoff during peak rainfall conditions, causing overflow in several locations. Four critical channels were identified, namely Channel 2, Channel 6, Channel 8, and Channel 13. Optimization was carried out by redimensioning the channels through increasing the width and depth to improve their flow capacity. The results show that the proposed channel redimensioning improves the hydraulic performance of the drainage system. After optimization, the water flow can be conveyed within the channel cross-sections without causing overflow. Therefore, the proposed improvement is expected to reduce the risk of flooding and improve the effectiveness of the drainage system in the Plaza Renon area.